Does private tutoring improve student learning in China? Evidence from the China Education Panel Survey. Issue 3 (25th September 2020) - Guo, Yuhe; Chen, Qihui; Zhai, Shengying; Pei, Chunchen
Abstract: Based on data from the China Education Panel Survey, which covers 28 counties/districts of China, this study applies a difference‐in‐differences method (combined with propensity score matching in some analyses) to estimate the impacts of private tutoring on students' learning outcomes. Our analyses yield three important findings. First, subject‐specific tutoring has a statistically significant and positive effect on Grade 8 students' scores on Chinese and mathematics tests, although the effects are modest in size. Second, private tutoring improves students' academic performance mainly through enhancing their test‐taking skills or deepening their understanding of subject‐specific knowledge, rather than improving their general cognitive skills. Finally, the effect of private tutoring is heterogenous across different subsamples: it is larger for female students, low‐performing students, and students with better‐educated and wealthier parents.